The The Correlation between Anti-Cytomegalovirus and AntiToxoplasma gondii Antibodies with the Plasma Level of Glycosylated Hemoglobin - Haghighi, Mehrdad; Goudarzi, Mehdi; Sistanizad, Mohammad; Pourheidar, Elham (Novelty in Biomedicine, 2022)
Background: Viral infections play an important role in the pathogenesis of diabetes mellitus (DM). The association between some viral infections, including cytomegalovirus (CMV) and the development of DM was reported by some articles, but about T. gondii data is limited. We aimed to evaluate the correlation between antiCMV and anti-Toxoplasma gondii (T. gondii) antibodies with the plasma level of glycosylated hemoglobin (HbA1C). Materials and Methods: This is a cross-sectional retrospective study conducted on the medical records of women who tested for pre-pregnancy checkups and had antibody levels against CMV and/or T. gondii, and plasma level of HbA1C. Results: During 4 years, data from 117 patients with anti-CMV IgG, and 186 with anti-T. gondii IgG was finally analyzed. According to the data, we did not detect any correlation between the plasma levels of HbA1C and IgG levels against CMV (Correlation Coefficient 0.150, p = 0.108) and T. gaondii (Correlation Coefficient 0.076, p = 0.300). Conclusion: In conclusion, we recommended a large-scale controlled clinical trial to compare the plasma level of HbA1C between patients with confirmed CMV or T. gondii infection and the control group.